Application of Frailty Index in Anthropological Material: Two 17th-18th Century Vilnius Cases - Paliulytė, Emilija (Vilnius University Open Series, 2024)
In recent years, a new method of measuring stress and frailty in archaeological populations has been developed – the Skeletal Frailty Index (SFI), which can determine changes in the overall health of past people through time. This study considers the applicability of the skeletal frailty index (SFI) in anthropological material by comparing 13 biomarkers of stress between two different 17th-18th century Vilnius communities (Algirdas St. 48C and Subačius St. 7). A sample of 187 individuals (Subačius St. 7, n=105, Algirdas St. 48C, n= 82) between the ages of 18 and over 45 years old was examined. Anova: single factor programme in Excel showed statistically significant differences between the two groups, with Subačius St. 7 individuals (SFI=3,86), who based on archaeological records were the commoners, exhibiting higher frailty than the Algirdas St. 48C individuals (SFI=2,23), who are thought to be the poorest members of society. These differences are explained by the osteological paradox, “cumulative effect” and migration factors. No statistically significant results (p>0.05) were found between female and male individuals in both communities. However, statistically significant results were found between different age groups (p
Keywords: Skeletal Frailty Index (SFI); 17th–18th century; Vilnius; Algirdo st. 48C; Subačius st. 7